Invertibility properties of matrix wiener‐hopf plus Hankel integral operators - Bogveradze, Giorgi; Castro, Luís P. (Mathematical Modelling and Analysis, 2008)
We consider matrix Wiener‐Hopf plus Hankel operators acting between Lebesgue spaces on the real line with Fourier symbols presenting some even properties (which in particular include unitary matrix‐valued functions), and also with Fourier symbols which contain sectorial matrices. In both situations, different conditions are founded to ensure the operators invertibility, one‐sided invertibility, Fredholm property, and the so‐called nand d‐normal properties. An example is provided to illustrate the proposed theory. First Published Online: 14 Oct 2010